VEGFR2 Expression Is Differently Modulated by Parity and Nulliparity in Mouse Ovary. (16th September 2018) - Di Nisio, Valentina; Rossi, Gianna; Iorio, Roberto; Pellegrini, Cristina; Macchiarelli, Guido; Tiboni, Gian Mario; Petricca, Sabrina; Cecconi, Sandra
Abstract : Parity and nulliparity exert opposite effects on women's health, as parity is considered a protective factor for several reproductive diseases. This study is aimed at determining if ovarian VEGF and VEGFR2 expression are differently modulated in the ovaries of parous and nulliparous mice. To this end primiparous and nulliparous fertile mice were sacrificed at postovulatory stage. Whole ovaries, corpus luteum, and residual stromal tissues were analyzed to assess VEGF/VEGFR2 expression levels. Ovarian mRNA amounts of Vegfa ( 120 and 164 ) and Vegfr2 were comparable between primiparous and nulliparous mice; both isoforms and receptor were accumulated mainly in corpus luteum tissues. VEGF 120 and 164 protein accumulation and distribution mirrored that of mRNA. Conversely, VEGFR2 protein content was significantly higher in ovaries of nulliparous mice and was more efficiently phosphorylated in ovaries of primiparous mice. In both groups, VEGFR2 was preferentially expressed in corpus luteum, while its phosphorylated form was equally distributed in two somatic compartments. We suggest that parity influences VEGFR2/phospho-VEGFR2 expression and tissue distribution. This difference could be part of a more complex mechanism that at least in mice is activated after the first pregnancy and likely aims to preserve female health.